KOMUNIKASI PERSUASIF GURU PADA ANGGOTA GENG PELAJAR DALAM PROGRAM PETUAH (PESANTREN SABTU AHAD) DI MAN YOGYAKARTA II TAHUN 2014 - Fajar Yusuf Baktiar (IlKom 15 UMY 329, 2015)
*329 The gang phenomenon among students is a latent problem that is quite disturbing. Likewise with gang activity maneuver, the gang of students in Yogyakarta MAN II whose activities lead to more acts of vandalism that damage. In the framework of the handling of the gang activity, MAN Yogyakarta II established a program of activities called PETUAH (Pesantren Sabtu Ahad). The phenomenon of PETUAH program be interesting to study, which is to examine how pesuasive communication of teachers on student gangs in the program. So the goal of this research is to describe the communication peruasif teachers on student gangs. The benefits of this research in an effort to minimize gang activity by madrassas students who possess gang in madrassas so that problems do not recur ever existed. The author uses descriptive qualitative research approach, because this study aimed to describe the phenomenon in detail through data collection profusely. The authors use data triangulation technique to determine the validity of the data in this study. The conclusion from this study is that there are two persuasive communication techniques used in PETUAH programe, technic of experts question and technic of time pressure. In presenting the material, the teacher uses verbal and non verbal language and the use of audio-visual media so that the message is more easily grasped by students